Antidumping and the global financial crisis : the impact on Latin America and the Caribbean - Feinberg, Robert M. (UN ECLAC Washington, D.C.US, 2010)
Updates the earlier study by Feinberg (2006) which analysed the trends in US antidumping actions against LAC between 1980 and 2004. Examines the current patterns of protection in response to the global recession. Focuses on cases files by LAC and targetting LAC, but global issues are addressed as well.